Theory and Practice of Intercultural Communication - Kalizhanova, A.N. (Karagandy University of the name of acad. E.A. Buketov, 2023)
This educational guide is intended for students of the educational program "6B02301–Translation Studies" studying by credit technology and explores relevant concepts, attitudes, and skills. Students develop awareness and competence in effective communication in culturally diverse settings. The topics include theories of culture and diversity, verbal and nonverbal intercultural communication, prejudice, discrimination, ethnocentrism, and adapting to new cultures. Competence and practice in intercultural communication skills are emphasized.